An Analysis Of Code Swithcing Used On Puella’s Video Youtube Channel By Cinta Laura With Yosi Sudarso: Penelitian - Evi Lestaria; Desi Purnama Sari; Humaira Syahmidi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the phenomenon of code-switching in the YouTube video series on Puella’s channel, featuring Cinta Laura and Yosi Sudarso. Code-switching refers to the practice of alternating between two or more languages or dialects within a conversation, which is often used for emphasis, cultural expression, or convenience. In this analysis, we examine the contexts in which Cinta Laura and Yosi Sudarso switch between Indonesian, English, and sometimes other languages, and how this practice reflects their identities, communication styles, and the social dynamics of their audience. The study identifies specific instances of code-switching, categorizing them into situational, conversational, and social purposes, and discusses the role of code-switching in fostering a more casual, relatable, and dynamic interaction between the hosts and their viewers. By analyzing these linguistic choices, this research offers insights into how bilingual individuals navigate their linguistic resources in a media-driven environment and how language choice can enhance communication and engagement in digital platforms.